(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of price and consumer trust on purchasing decisions in TikTok Shop. The research involved 164 respondents from Management students at PGRI Semarang University who have experience with TikTok Shop. Using Structural Equation Modeling (SEM) with AMOS, the findings indicate that consumer trust significantly affects purchasing decisions. This study provides insights into enhancing marketing strategies on social commerce platforms by emphasizing pricing strategies and building consumer trust to encourage purchasing behavior.